2011
DOI: 10.1021/la200670w
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Adsorption at the Metal–Oil Interface

Abstract: The structure of the adsorbed palmitic acid at the Fe oxide/oil interface has been investigated using polarised neutron reflectometry. The palmitic acid was found to be strongly adsorbed at the oxide/oil interface resulting in a monolayer of thickness 16±4 Å for 150, and 500 ppm palmitic acid concentrations (16±5 Å for the 1000 ppm solution). These layer thicknesses suggest tilt for the palmitic acid molecules with respect to the interface. The model also requires a second diffuse layer extending in the bulk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 9 publications
3
33
0
Order By: Relevance
“…This is supported by the PNR results reported here, which indicate a layer thickness close to that of the extended oleic acid molecule, whereas PNR layer thicknesses for palmitic acid suggest it sits at an angle 17 .…”
Section: Pnrsupporting
confidence: 85%
“…This is supported by the PNR results reported here, which indicate a layer thickness close to that of the extended oleic acid molecule, whereas PNR layer thicknesses for palmitic acid suggest it sits at an angle 17 .…”
Section: Pnrsupporting
confidence: 85%
“…These include the surface forces apparatus (SFA) [58][59][60][61], atomic/lateral force microscope (AFM/LFM) [62][63][64][65], quartz crystal microbalance (QCM) [66], ultrathin film interferometry (UTFI) [67], neutron reflectometry [68,69] and various surface-specific vibrational spectroscopies [70][71][72]. Methods were also developed to generate model close-packed monolayers by chemical grafting of self-assembled alkylthiols and alkyl siloxanes on solid surfaces [73][74].…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…This has been used to determine the thickness of acetic acid films adsorbed on iron and copper from polyalphaolefin (PAO) [69] and of palmitic acid adsorbed on iron oxide [68] and DLC [89] from hexadecane and PAO respectively. Films indicative of tilted monolayers were detected on the metals and most DLCs.…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 99%
“…This has been successfully applied to a range of materials, such as iron [65,73,74], copper [10], titanium [41], nickel [75], chromium [76], zirconium [77], ITO [78], stainless steel [76] and various other alloys [79][80][81][82]. Care should be taken during deposition and subsequent handling to ensure that the final surface represents the material desired: for example to what extent it oxidises upon exposure to air.…”
Section: Substratesmentioning
confidence: 99%
“…Despite the importance of iron and steel across a wide range of industrial applications, they remain relatively unstudied as a surface by neutron reflectometry, although a small but significant body of work concerning surfactant adsorption at iron/liquid interfaces does exist [65,73,75,[101][102][103]. The direct study of steel alloys is slightly more challenging due to the necessity of preparing thin (to ensure neutron transmission) and very flat films, although recent work has demonstrated that representative stainless steel films can be prepared using electron-beam deposition at low pressures [76].…”
Section: Iron and Steelmentioning
confidence: 99%